Motivational interviewing early after acute stroke: a randomized, controlled trial - Watkins, Caroline L; Auton, Malcolm F; Deans, Carol F; Dickinson, Hazel A; Jack, Cathy I A; Lightbody, C Elizabeth; Sutton, Christopher J; van den Broek, Martin D; Leathley, Michael J (Stroke (1970), 2007)
The purpose of this study was to determine whether motivational interviewing, a patient-centered counseling technique, can benefit patients' mood 3 months after stroke. A single-center, open, randomized, controlled trial was conducted at a single hospital with a stroke unit. Subjects consisted of 411 consecutive patients on the stroke register who were over 18 years of age and who did not have severe cognitive and communication problems that would prevent them from taking part in an interview; were not known to be moving out of the area after discharge; and were not already receiving psychiatric or clinical psychology intervention. All patients received usual stroke care. Patients in the intervention group received 4 individual, weekly sessions of motivational interviewing with a trained therapist in addition to usual stroke care. The primary outcome was the proportion of patients with normal mood at 3 months poststroke measured by the 28-item General Health Questionnaire (normal, <5; low > or=5) using a mailed questionnaire. Eighty-one of 207 (39.1%) patients in the control group and 100 of 204 (49.0%) patients in the intervention group had normal mood at follow up. A significant benefit of motivational interviewing over usual stroke care (OR: 1.60, 95% CI: 1.04 to 2.46, P=0.03) was found. Our results suggest motivational interviewing leads to an improvement in patients' mood 3 months after stroke.